Experience of Semantic-Cognitive Modeling of Religious Worldview in Languages of Different Structure (HARAM Concept) - P. A. Magomedova (Научный диалог)
The experience of reconstructing the religious (Islamic) concept as a value-cognitive and ideological constant is presented on the example of the concept HARAM/HIARAM in Russian and Avar linguistic cultures. The material for the study was data from lexicographic sources, paremiological funds of these languages, data from Russian and Avar texts (including translations) of spiritual literature; language data of the National Corpuses of the Russian and Avar languages. It is noted that the conceptual component of the concept under study reveals similarities in the compared linguocultures: the HARAM semantic model is represented by an obligatory component with a negative connotation 'everything that is bad, evil, sin > forbidden' [certain actions, deeds, objects and phenomena], and an optional component with a positive connotation: 'reserved place, forbidden [for everything bad] territory'. It is clarified that the value component of the concept is wider than in terms of an ordinary prohibition or taboo. It is shown that in the Muslim consciousness HARAM is a multicomponent concept with ambivalent semantics. Similarities and differences in the objectification of this concept may depend, first of all, on the specifics of the religious and linguistic consciousness of a person, his worldview; secondly, they can be conditioned by the discourse in which the concept is explicated, and hence the objectification takes place in different worldview (religious, everyday, etc.). The process of desacralization of the concept HARAM semantics is considered.